Performance analysis of the first order linear stationary iterative methods in solving third order Newton-Cotes quadrature system - Muthuvalu, M.S. (2013)
In this paper, application of the first order linear stationary iterative methods is extended to solve third order composite closed Newton-Cotes quadrature (3-CCNC) system. The performances of tested iterative methods for the 3-CCNC system are comparatively studied by their application to solve the second kind linear Fredholm integral equations. The derivation and implementation of the methods are presented. In addition, simulation results of three test problems are included to verify the performance of the methods.